Posttraumatic Stress Disorder in the Nursing Population: A Concept Analysis. Issue 4 (31st July 2013) - Mealer, Meredith; Jones, Jacqueline
Abstract : Purpose: This article is a report of an analysis of the concept of posttraumatic stress disorder (PTSD) and its application to the nursing population. Background: Nurses are at an increased risk for work‐related stress resulting in retention issues and impaired functioning in work and home environment. The nursing discipline has been inconsistent with the concepts used to describe the distress and resultant discussions related to the comprehensive nature of the distress experienced, heavily focusing on existing medical language that emphasizes disorders and psychopathology. Review methods: Walker and Avant's strategy for concept analysis was used in this analysis. A literature review for 1994–2011 was conducted for the following keywords: secondary traumatic stress, compassion fatigue, vicarious traumatization, posttraumatic stress disorder, and nurse. Results: The concept of posttraumatic stress disorder in the nursing population is best described within the context of the Nurse as Wounded Healer theory. Essential attributes include intrusions, avoidance, and hyperarousal. The consequences include worldview changes, retention issues, sleep disruption, and social network disturbances. Conclusion: This concept analysis viewed through The Nurse as Wounded Healer lens, offers clarity to the concept of PTSD within the nursing population and identifies limitations to prior conceptualizations.